Horror effect technique through the application of ‘Film Language’ on four selected horror films - Addley Bromeo Bianus; Imelda Ann Achin; Zairul Anwar Md. Dawam; Rosli Sareya (International Journal of Technical Research and Application (IJTRA), 2014)
This research is to describe the application of Film Language in four selected horror films. This analysis refers to method done by the filmmakers in creating horror effect to audience through the use of Film Language. Research scope was limited to four horror films that were produced in 2007 and 2008. The four horror films were selected based on two selection criteria, i.e. the achievement of box office collection and questionnaires. The research result found that four components in Film Language i.e. cinematography, mise en scene, editing and audio have played big role in horror film genre not only from the technical aspect but also could influence the development of story plot of a horror film.